2014
DOI: 10.1093/bja/aeu227
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of the success rates of intubation and failed intubation airway rescue techniques in 7256 attempted intubations of trauma patients by pre-hospital physicians

Abstract: This is the largest series of physician pre-hospital tracheal intubation; the success rate of 99.3% is consistent with other reported data. All rescue airways were successful. Non-anaesthetists were twice as likely to have to perform a rescue airway intervention than anaesthetists. Surgical airway rates reported here (0.7%) are lower than most other physician-led series (median 3.1%, range 0.1-7.7%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
114
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 40 publications
10
114
2
2
Order By: Relevance
“…The ETI success rate of physicians in our group was 98.4%. This is comparable with data from other physician-staffed EMS series (99.1%) and with recent data from the United Kingdom (99.4%) [9,11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The ETI success rate of physicians in our group was 98.4%. This is comparable with data from other physician-staffed EMS series (99.1%) and with recent data from the United Kingdom (99.4%) [9,11].…”
Section: Discussionsupporting
confidence: 90%
“…Of these, 14 were performed without attempted laryngoscopy by the HEMS physicians. This primary ESA rate (0.7%) is comparable with the rate of 0.6% reported by Lockey [11]. To compare these figures, the indications and standard operation protocols for performing these interventions must be evaluated.…”
Section: Discussionsupporting
confidence: 77%
“…The combination of competencies to assess the situation, practical skills and ability to manage complications are more important than the name of the provider's speciality. In a physician‐staffed helicopter emergency medical service in the UK, where doctors are a mix of anaesthesiologists and emergency physicians, the success rates are still high and complications are low 10. This is probably related to the strict training and highly standardised operating procedures that all doctors must adhere to.…”
mentioning
confidence: 99%
“…This is consistent with previous papers where it was considered difficult to predict survival outcomes using the ISS alone 11 12. The inaccuracy of predicting survival using ISS is further corroborated in the London HEMS observational study 1. These issues notwithstanding, ISS is commonly used as an international measure for defining major trauma and predicting mortality and was therefore useful to measure UK military prehospital performance against other systems.…”
Section: Discussionmentioning
confidence: 90%
“…A study of patients over a 21-year period (1991–2012) suggested that surgical airway procedures were performed on average 2.4 times per year by a busy UK inner city Helicopter Emergency Medical team;1 but because of the nature of conflict, surgical airway procedures tend to be more common in combat scenarios 2 3. Airway compromise accounts for up to 2% of combat deaths2 and is the third leading cause of potentially preventable death in a combat zone 4.…”
Section: Introductionmentioning
confidence: 99%